The low cost phenomenon - EASYJET (2013)
LCC Market Development - In 1996 low cost airlines (LCCs) accounted for only 1.4% of intra-European Union capacity. By the end of 2002, low cost airlines had captured 12% of all intra-EU capacity - Currently LCCs have a 30% market share of scheduled European point-to-point passengers. According to AEA forecasts, the LC market is expected to increase to 43% of European traffic by 2011. - In 2006 140 million passengers were carried by LCCs. - Low-fare airlines have increased their presence from 13% of city pairs in 2003 to 26% in 2007. 96% of new city-pairs between 2005 and 2007 were added by LCCs. - The United Kingdom still sees the highest number of low-cost flights, followed by Spain, which has been making up a lot of ground over the last year. This is followed by Italy and Germany with slightly fewer flights. These four countries contribute to roughly three quarters of low-cost departures. France is fifth in this list with only 5% of LC flights. - easyJet and Ryanair continue to be the biggest players in the European LCC market accounting for about 40% of all LCC capacity. The top two are followed by Airberlin, which contributes another 10% leaving three carriers in control of half the European low-cost market.